Beneficial effect of Lactococcus lactis NCC 2287 in a murine model of eosinophilic esophagitis. Issue 12 (9th August 2016) - Holvoet, S.; Doucet‐Ladevèze, R.; Perrot, M.; Barretto, C.; Nutten, S.; Blanchard, C.
Abstract: Background: Eosinophilic esophagitis (EoE) is a severe inflammatory disease of the esophagus which is characterized histologically by an eosinophilic infiltration into the esophageal tissue. The efficacy of probiotics in the context of atopic diseases has been well investigated but, to date, there has been no study which has evaluated probiotic effects on EoE inflammation. This study sought to identify a probiotic which improves esophageal inflammation in experimental EoE. Methods: Two candidate probiotics, Lactococcus lactis NCC 2287 and Bifidobacterium lactis NCC 2818, were tested in a murine model of EoE elicited by epicutaneous sensitization with Aspergillus fumigatus protein extract. Administration of bacterial strains in drinking water was used, respectively, as a preventive or treatment measure, or continuously throughout the study. Inflammatory parameters were assessed in the esophagus, skin, and lungs after allergen challenge. Results: In this EoE model, supplementation with L. lactis NCC 2287 significantly decreased esophageal and bronchoalveolar eosinophilia but only when given as a therapeutic treatment. No significant effect on eosinophilia was observed when NCC 2287 was given as a preventive or a continuous intervention. NCC 2287 supplementation had no significant effect on immunoglobulin levels, skin symptom scores, or on transepidermal water loss. Supplementation with another probiotic, B. lactis NCC 2818, had no significant effect on esophageal eosinophilia. Conclusion: We identified a L. lactis strain, able to attenuate esophageal eosinophilic inflammation in a preclinical model of EoE. This effect is strain specific and depends on the timing and duration of bacterial supplementation. Confirmation of these observations in human clinical trials is warranted.